The Community Mausoleum in North Bergen (New York), where the ashes of Kudlich were kept till they where transferred to the Kudlich-house at Lobenstein (Schlesien)
The Community Mausoleum in North Bergen (New York), where the ashes of Kudlich were kept till they where transferred to the Kudlich-house at Lobenstein (Schlesien).